2 - Socioeconomic Characteristics and Satisfaction of Tenants in Public Housing in Lagos, Nigeria - Jiboye, Adesoji David (Africa Development, 2021)
This study examined the relationship between the socioeconomic characteristics (such as sex, age, marital status, religion, ethnicity, occupation, educational status, income level and household size) of public housing tenants and their housing satisfaction in Lagos, Nigeria. A survey of six randomly selected housing estates was carried out from the existing public housing estates in the study area. Using systematic sampling technique, 10 per cent of the housing units, totalling 1022 households, were sampled. Data were analysed by simple descriptive statistics and Pearson correlation coefficients. The study showed that age, education, income, marital status, occupation and house-hold size correlated significantly with tenants’ housing satisfaction in Lagos. It also showed that other socioeconomic variables such as sex, religion and ethnic origin of the respondents are not significantly correlated with housing satisfaction. The study highlighted the need for policy makers on public housing to consider people’s socioeconomic parameters when planning for new housing.